Effects of ethanol storage and lipid extraction on stable isotope compositions of twelve pelagic predators - Shen, Yongfu; David, Mboglen; Gong, Yi; Wu, Feng; Li, Yunkai (Frontiers in Marine Science, 2023)
Stable isotope analysis (SIA) has proven to be a powerful tool in reconstructing diets and characterizing trophic relationships for pelagic predators. Ethanol has been a common preservative solution for biopsy samples from remote areas and archived collections. It is still under debate whether the effects of ethanol (ET) would bias the trophic interpretation of the stable isotope values. Further, lipid extraction (LE) is becoming more popular as a general treatment for standardization prior to SIA, particularly for investigating intra and interspecific variation of sympatric species, because lipids have lower δ13C values. In this study, the long-term (up to 448 days) effects of treatment ET and combined treatments ET and LE (ET+LE) on stable carbon and nitrogen isotope values (δ13C and δ15N, respectively) of twelve pelagic predators from the open ocean were evaluated. Results showed that compared with control values, δ15N values displayed a positive change (δ15Nmean offset was 0.71 ± 0.56‰) but δ13C values had variable results (δ13Cmean offset was 0.42 ± 0.64‰) among all species following treatment with ET during the first 28 days and then remained stable throughout the experiment. Compared with treatment LE results, no difference was observed in δ13C, δ15N values, and C/N ratios through time following treatment ET+LE. These results indicated that treatment ET may have species-specific effects on stable isotope values, and the shifts from treatment LE could counter the changes caused by treatment ET. In addition, after 28 days of preservation, the values following treatment ET were similar to those following treatment LE in low C/N species (C/N<3.5), which suggested ethanol may also affect some of lipid contents from muscle tissues. Nevertheless, further research is needed to focus on the mechanisms that control changes in stable isotope composition in tissues stored in ethanol. Given the effects on pelagic predators, muscle tissue samples stored in ethanol from the open ocean or a museum after LE treatment could be used to develop SIA.